2023
DOI: 10.1001/jamanetworkopen.2023.46216
|View full text |Cite
|
Sign up to set email alerts
|

Acceptance and Commitment Therapy Among Informal Caregivers of People With Chronic Health Conditions

Fen Ye,
Jung Jae Lee,
Dandan Xue
et al.

Abstract: ImportanceAlthough there is substantial evidence to suggest the health benefits of acceptance and commitment therapy (ACT) among informal caregivers of people with chronic health conditions, the great variation in intervention designs among published studies limits its application.ObjectivesTo identify intervention characteristics of ACT that are associated with improved psychological health and to assess the acceptability of ACT among informal caregivers.Data SourcesSeven English- and 3 Chinese-language datab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 81 publications
(276 reference statements)
0
1
0
Order By: Relevance
“…29 Acceptance and commitment therapy, which focuses on increasing psychological flexibility to improve mental health outcomes, showed high feasibility and acceptability but mixed outcomes in a recent systematic review of trials in the caregiving stress context, but methodological limitations, including a lack of studies in US Hispanic people or stroke caregivers, suggest the need for additional research. 30 We noted demographic differences in MA and NHW stroke caregivers, namely that MA caregivers were on average 5 to 6 years younger, more often female, and not married compared with NHW caregivers. These findings are in line with the results from a national study of caregivers for adults aged ≥50 years, which found that Hispanic caregivers were younger, less likely to be married, and more likely to have young children or grandchildren in the household, as well as a more recent report from the National Study of Caregiving and Hispanic Established Populations for the Epidemiologic Studies of the Elderly, which also noted the younger age and preponderance of female caregivers.…”
Section: Discussionmentioning
confidence: 74%
“…29 Acceptance and commitment therapy, which focuses on increasing psychological flexibility to improve mental health outcomes, showed high feasibility and acceptability but mixed outcomes in a recent systematic review of trials in the caregiving stress context, but methodological limitations, including a lack of studies in US Hispanic people or stroke caregivers, suggest the need for additional research. 30 We noted demographic differences in MA and NHW stroke caregivers, namely that MA caregivers were on average 5 to 6 years younger, more often female, and not married compared with NHW caregivers. These findings are in line with the results from a national study of caregivers for adults aged ≥50 years, which found that Hispanic caregivers were younger, less likely to be married, and more likely to have young children or grandchildren in the household, as well as a more recent report from the National Study of Caregiving and Hispanic Established Populations for the Epidemiologic Studies of the Elderly, which also noted the younger age and preponderance of female caregivers.…”
Section: Discussionmentioning
confidence: 74%